Analysis the Impact of Liquidity, Profitability, Activity and Solvency Ratio on Change in Earnings - Lutfi Baraja; Eka Agfa Yosya (Indonesian Management and Accounting Research, 2018)
This study aims to determine the impact of liquidity, profitability, solvency, and activity ratio on change in earnings. In this research, multiple linear regression is used to identify a change in earnings on an entity. The sample data are taken from consumer goods of manufacturing company listed on BEI for the period 2014-2017. The results of this study show net profit margin as profitability ratio have a significant effect on change in earnings. The other results show liquidity ratio measured by current ratio, activity ratio measured by total asset turnover, and solvency ratio measured by debt to equity ratio has an insignificant effect on change in earnings.Keywords:    Activity Ratio, Current Ratio, Debt To Equity Ratio, Net Profit Margin, Liquidity Ratio, Profitability Ratio, Solvency Ratio, Total Asset Turnover, Change In EarningsJEL Classification